Proposed Improvement of Monitoring and Controlling Process on Outstanding Customer (Study Case: XYZ Company in Jambi Area) - Asih Aulia Putri; Heriyono Lalu; Sri Widaningrum; Wiyono Sutari (School of Industrial and System Engineering, Telkom University, 2022)
PT XYZ is a company that provides telecommunications services, and for corporate customers, thereis the BGES Unit. The payment process for corporate customers is managed by one of the BGESpillars, namely Collection Management. One of the tasks that Collection Management takes care ofis outstanding data. The achievement of outstanding billing is only 14.75% per year, which means apayment delay of IDR 7,000,458,871.00 in 2021. Due to excessive workload, billing managementdoes not supervise customers regarding billing so billing objectives are not achieved. In addition,billing information in the form of invoices is provided later than the 5th through 12th of each monthso that customers do not know for sure the total bill. This research aims to make improvements in themonitoring and controlling processes of customer outstanding billing. This research uses the businessprocess improvement method. This method also refers to a process that works but some activitiesneed improvement. It does not design new activities but improves existing activities. The tools ofbusiness process improvement that were used in this research are application technique wheels andstreamlining, which can be useful for simplifying a process and fixing a problem based on theoutstanding billing problems by PT XYZ. The result of this research is a new business process as isdashboard monitoring and controlling shown by a context diagram that contains incoming andoutgoing data on the billing information system and reminder notification will appear if the target isnot achieved. The new business process is expected to assist the BGES unit in monitoring andcontrolling customers every month, and the target that is expected to be achieved is an outstandingfigure of less than 1,000,000 by the end of the year.